Evaluating the Environmental Impact of Mining: Procedures, Outcomes, and Sustainable Remediation - V. Basil Hans; Swathi Bhat (International Journal of Minerals, 2025)
Mining is necessary for economic growth and getting resources, yet also has a big impact on the environment. This article looks at the different ways that mining affects the environment, such as land degradation, deforestation, water pollution, air pollution, and loss of biodiversity. Mining on the surface and underground can cause soil erosion, damage ecosystems, and pollute groundwater and surface water with heavy metals and harmful compounds. Furthermore, the emission of particulate matter and greenhouse gases aggravates climate change and presents health hazards to adjacent communities. The report also talks about ways to reduce the damage done by mining, such as using sustainable mining methods, keeping an eye on the environment, and restoring mined lands. To minimise the ecological impact of mining and encourage sustainable resource management, it is important to find a balance between economic needs and environmental protection.
Keywords: Land degradation; air pollution; and sustainable mining; loss of biodiversity; water pollution